2004
DOI: 10.1007/s00213-004-1833-7
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate restores visual memory, but not working memory function in attention deficit-hyperkinetic disorder

Abstract: Our results suggest that current conceptualisations of the neuropsychological basis of AD-HKD and the proposed therapeutic mechanisms of MPH require broadening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
92
3
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 61 publications
12
92
3
2
Order By: Relevance
“…Despite the lack of significant findings on the primary outcomes, the improvement on BVMTR and CVLT2 is intriguing, particularly in light of the concordance of these analogous measures of visual and verbal memory consolidation in the absence of any other significant outcomes. Previous research has revealed some positive benefits of amphetamine on memory and sustained attention in attention-deficit/hyperactivity disorder [26,27], schizophrenia [28], and traumatic brain injury [29] populations. However, the mechanism by which L-amphetamine improves auditory/verbal and visual/spatial memory is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of significant findings on the primary outcomes, the improvement on BVMTR and CVLT2 is intriguing, particularly in light of the concordance of these analogous measures of visual and verbal memory consolidation in the absence of any other significant outcomes. Previous research has revealed some positive benefits of amphetamine on memory and sustained attention in attention-deficit/hyperactivity disorder [26,27], schizophrenia [28], and traumatic brain injury [29] populations. However, the mechanism by which L-amphetamine improves auditory/verbal and visual/spatial memory is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…These tasks were chosen because they have been extensively validated in both child and adult populations (Curtis, Lindeke, Georgieff & Nelson, 2002;Luciana & Nelson, 1998;Rhodes, Coghill, Matthews, 2004, 2006Robbins et al, 1994) and typical developmental trajectories of performance have been reported (Curtis et al, 2002;Luciana & Nelson, 1998;Robbins et al, 1994). Tasks are performed on a touch-screen computer and are highly suitable for use with children and adolescents (Rhodes et al, 2005;Rhodes, Riby, Matthews & Coghill, 2011).…”
Section: Cognitive Tasksmentioning
confidence: 99%
“…One clue to mechanisms of efficacy can be found at a behavioral level, where methylphenidate improves academic performance (Yang et al 2004;McGough et al 2006), working (Wright and White 2003) and visual (Rhodes et al 2004) memory, nonverbal (O'Toole et al 1997) and visuospatial (Bedard et al 2004) learning, and reading skills (Keulers et al 2007), which may explain why, in addition to its medicinal use, it is used illegally by healthy students to aid study (Teter et al 2006). Despite evidence of methylphenidate-induced changes in learning and memory, the mechanisms underlying these changes have received little focus and are commonly assumed to be a by-product of improved attention.…”
mentioning
confidence: 99%
“…Indeed, recall that long-term methylphenidate treatment has been shown to improve working (Wright and White 2003) and visual memory (Rhodes et al 2004), nonverbal (O'Toole et al 1997) and visuospatial learning (Bedard et al 2004), and reading skills (Keulers et al 2007). It has also been found to attenuate memory deficits in Alzheimer's disease (Kittur and Hauser 1999) and improve learning in children left with learning deficits following cancer (Thompson et al 2001).…”
mentioning
confidence: 99%